Deciphering the natural history of SCA7 in children. (23rd July 2020) - Bah, M. G.; Rodriguez, D.; Cazeneuve, C.; Mochel, F.; Devos, D.; Suppiej, A.; Roubertie, A.; Meunier, I.; Gitiaux, C.; Curie, A.; Klapczynski, F.; Allani‐Essid, N.; et al.
Abstract : Background and purpose: Childhood‐onset autosomal dominant cerebellar ataxia type 7 (SCA7) is a severe disease which leads to premature loss of ambulation and death. Early diagnosis of SCA7 is of major importance for genetic counselling and still relies on specific genetic testing, driven by clinical expertise. However, the precise phenotype and natural history of paediatric SCA7 has not yet been fully described. Our aims were to describe the natural history of SCA7 in a large multicentric series of children of all ages, and to find correlates to variables defining this natural history. Methods: We collected and analysed clinical data from 28 children with proven SCA7. All had clinical manifestations of SCA7 and either a definite number of CAG repeats in ATXN7 or a long expansion > 100 CAG. Results: We identified four clinical presentation patterns related to age at onset. Children of all age groups had cerebellar atrophy and retinal dystrophy. Our data, combined with those in the literature, suggest that definite ranges of CAG repeats determine paediatric SCA7 subtypes. The number of CAG repeats inversely correlated to all variables of the natural history. Age at gait ataxia onset correlated accurately to age at loss of walking ability and to age at death. Conclusion: SCA7 in children has four presentation patterns that are roughly correlated to the number of CAG repeats. Our depiction of the natural history of SCA7 in children may help in monitoring the effect of future therapeutic trials.